Noninvasive tumor hypoxia measurement using magnetic resonance imaging in murine U87 glioma xenografts and in patients with glioblastoma. Issue 5 (24th June 2013) - Linnik, Inna V.; Scott, Marietta L. J.; Holliday, Katherine F.; Woodhouse, Neil; Waterton, John C.; O'Connor, James P. B.; Barjat, Hervé; Liess, Carsten; Ulloa, Jose; Young, Helen; Dive, Caroline; Hodgkinson, Cassandra L.; et al.
<x xml:space="preserve">Abstract</x> Purpose There is a clinical need for noninvasive, nonionizing imaging biomarkers of tumor hypoxia and oxygenation. We evaluated the relationship of T1‐weighted oxygen‐enhanced magnetic resonance imaging (OE‐MRI) measurements to histopathology measurements of tumor hypoxia in a murine glioma xenograft and demonstrated technique translation in human glioblastoma multiforme. Methods Preclinical evaluation was performed in a subcutaneous murine human glioma xenograft (U87MG). Animals underwent OE‐MRI followed by dynamic contrast‐enhanced MRI (DCE‐MRI) and histological measurement including reduced pimonidazole adducts and CD31 staining. Area under the curve (AUC) was measured for the R1 curve for OE‐MRI and the gadolinium concentration curve for DCE‐MRI. Clinical evaluation in five patients used analogous imaging protocols and analyses. Results Changes in AUC of OE‐MRI (AUCOE) signal were regionally heterogeneous across all U87MG tumors. Tumor regions with negative AUCOE typically had low DCE‐MRI perfusion, had positive correlation with hypoxic area (P = 0.029), and had negative correlation with vessel density (P = 0.004). DCE‐MRI measurements did not relate to either hypoxia or vessel density in U87MG tumors. Clinical data confirmed comparable signal changes in patients with glioblastoma. Conclusion These data support further investigation of T1‐weighted OE‐MRI to identify regional tumor hypoxia. The quantification of AUCOE has translational potential as a clinical biomarker of hypoxia. Magn Reson Med 71:1854–1862, 2014. © 2013 Wiley Periodicals, Inc.